Characterization of Secondary Metabolites in Two Cousinia species - Leyla Paşayeva; Hanifa Fatullayev; İrem Nur Karakuş; Serap Soylu; Osman Tugay (International Journal of Secondary Metabolite)
Cousinia is one of the widespread genera of Asteraceae family. According to previous studies on some Cousinia species it was found that these species are rich of triterpenes, sesquiterpenes, flavonoids, acetylenes and steroids. According to our knowledge, there are no published reports on the chemical composition of C. iconica Hub. - Mor. and C. aintabensis Boiss. & Hausskn., thus we aimed to investigate secondary metabolites of these species. In this study, the phytochemical constituents of these species were evaluated. Seven of identified compounds were quantified. The quantitative and qualitative determination of compounds within the extracts was carried out by LC-MS/MS.  Phytochemical analyses revealed the presence of flavonoids, saponins, terpenes and steroids. Preliminary examination of the mass spectrums revealed the presence of phenolic acids and derivatives and flavonoid compounds in extracts. According to quantitative analyses the main compound of C. iconica (CI) and C. aintabensis (CA) extracts was rutin with the highest contents (169.779 µg/mgextract and 161.638 µg/mgextract). Moreover, qualitative and quantitative study combined with different biological activities will shed new lights to the advanced studies.